EFFECT OF THE PROBLEM BASED LEARNING (PBL) MODEL ON THE STUDENT CRITICAL THINKING SKILL ON EXCRETORY SYSTEM MATERIAL IN CLASS XI SMA NEGERI 1 DOLOK PANRIBUAN ACADEMIC YEAR 2023/2024 - Napitupulu, Andri Marusaha; Sidabutar, Hudson (Jurnal Pelita Pendidikan, 2025)
This research aims to obtain related information; The influence of the PBL model on critical thinking skills at SMA Negeri 1 Dolok Panribuan. This research is a type of quasi experiment research. This research was carried out at SMA Negeri 1 Dolok Panribuan Simalungun Regency. Samples were taken by proportional random sampling technique. The data collection method uses critical thinking skills questions consisting of pretest and posttest. The effect of the PBL learning model on students' critical thinking skills at SMA Negeri 1 Dolok Panribuan is as follows: There is a comparison of the results of posttest calculations in the control class and the experimental class with the Independent Sample T-Test to obtain the results of the t-table > t-calculation value of 2.998 > 1.997 with α = 5% where based on the results of the t-test it can be concluded that there is an influence of the Problem Based Learning (PBL) model on Students' Critical Thinking Skills on System Materials Excretion at SMA Negeri 1 Dolok Panribuan. The PBL learning model is better used for student learning outcomes with an average score of 83.25 than the conventional learning model with an average score of 76.00.